IMPOLITENESS STRATEGIES USED BY NETIZENS TOWARDS TASYI ATHASYIA ON INSTAGRAM - Afriana, Afriana; Mubarak, Zia Hisni (Asosiasi dosen IDEBAHASA KEPRI, 2024)
Social media sites like Instagram, let people communicate worldwide, share ideas and opinions, and keep up with current affairs, have become an essential part of people’s everyday life in the current digital era. However, with the increasing use of Instagram, there has been a noticeable rise in impoliteness and incivility in online communication as the anonymity that social media provides has emboldened individuals to express opinions that they might not typically voice in person encounters. This study aims to analyze the impoliteness strategies used by netizen on account tasyiiathasyia’s posting on Instagram. The design of this study is qualitative method. This study used observational method and non-participatory technique. The data was obtained on Instagram from tweets written by netizens then collected and analyzed by using Culpeper Theory (1996). The results, there are five impoliteness that discussed in this study, there are 2 data that related to bald on record impoliteness, 3 data positive impoliteness, 1 data negative impoliteness, 4 data sarcasm or mock impoliteness and no data related to withhold politeness.